Pengaruh Penerapan Sistem Informasi Akuntansi Dan Kualitas Sistem Informasi Akuntansi Terhadap Kinerja Pegawai Di PT Simatelex Batam - Natalia Sitohang; Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2023)
The purpose of this study is to ascertain how end match affects implementing SIA and the quality of SIA on employee performance. The information gathering strategy is an overview survey of 100 respondents. The method used is the Non Probability Sampling technique that is selected by Saturated Sampling (census), which is a sampling method when all members of the population are used as samples. The results of the hypothesis test, the value of tcount 5.861 > ttable value of 1.666 and a substantial amount of 0.000 is less than the alpha value of 0.05, so that it can be finished that the SIA Implementation employee performance is significantly and directly impacted by this variable.. tcount value of 4.177 > ttable value of 1.666 and a significant value of 0.000 is less than the alpha value of 0.05, so it can be concluded that the AIS quality variable has a direct and significant effect on employee performance. The calculated F value is and the sig value is 0.000 < 0.05. 187.828 > F Table 3.128, so the authors conclude that the SIA Implementation and SIA Quality have a significant or significant influence on Employee Performance.